A Comprehensive Evaluation of Peripheral Analgesic and Antipyretic Activities of Divalent Metal Complexes of Indomethacin (Dhaka University Journal of Pharmaceutical Sciences, 2018)
Comparative peripheral analgesic and antipyretic activities of copper, zinc, cobalt and manganese complexes of indomethacin were studied. Peripheral analgesic effect of the complexes was evaluated by following acetic acid-induced writhing inhibition method in mice whereas antipyretic activity was assessed by Brewer’s yeastinduced pyrexia in rat model. At 10- and 20-mg/kg doses, the zinc-indomethacin complex produced significant writhing inhibition (p